Measuring Competition: Inconsistent definitions, inconsistent results. - Linick, Matthew Allen (Education Policy Analysis Archives, 2014)
There is a developing literature examining how charter schools, through the effects of competition, impact performance in public school districts and district-run public schools, also known as the second-level effects of competition. What follows is an examination of how competition is measured in this literature that offers a critique of existing approaches to that measurement. Findings in these studies are problematized by inconsistent findings in other, similar studies; inconsistencies which may be due to inconsistent definitions and metrics of competition. I suggest a more specific definition of competition and suggest that other disciplines may offer guidance in the pursuit of a more consistent measurement of competitive effects.